2019
DOI: 10.1103/physreva.99.042513
|View full text |Cite
|
Sign up to set email alerts
|

Extensive high-resolution photoassociation spectra and perturbation analysis of the 2(0) long-range state of ultracold RbCs molecules

Abstract: We report high-resolution photoassociation (PA) spectra of RbCs in the 2(0 −) long-range state. Transitions to more than fifty vibrational levels were recorded with the largest binding energy being 507.5 cm −1. By fitting the experimental transition frequencies to the improved LeRoy-Bernstein formula, the C6 coefficient for the potential energy curve of the 2(0 −) state was determined to be −1509 ± 97 a.u.. Perturbation-induced energy level shift and state mixing of the long-range 2(0 −) and 3(1) states have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Hence, the molecular levels close to the dissociation threshold of the excited electronic states are firstly detected by PA spectroscopy kerman2004production. Some of the weakly bound levels are identified to belong to (2)0 + and (2)0 − states [in Hund's case (c) notation] which are studied in details [4][5][6]. Later, it is shown that the deeply bound levels in the electronically excited states can also be detected by PA spectroscopy [7],although the FC factor is expected to small.…”
mentioning
confidence: 99%
“…Hence, the molecular levels close to the dissociation threshold of the excited electronic states are firstly detected by PA spectroscopy kerman2004production. Some of the weakly bound levels are identified to belong to (2)0 + and (2)0 − states [in Hund's case (c) notation] which are studied in details [4][5][6]. Later, it is shown that the deeply bound levels in the electronically excited states can also be detected by PA spectroscopy [7],although the FC factor is expected to small.…”
mentioning
confidence: 99%